High-fat diet mouse model receiving L-glucose supplementations propagates liver injury - Amer, Johnny; Amleh, Athar; Salhab, Ahmad; Kolodny, Yuval; Yochelis, Shira; Saffouri, Baker; Paltiel, Yossi; Safadi, Rifaat (Frontiers in Nutrition, 2024)
Background & Aims: Limited data link manufactured sweeteners impact on metabolic dysfunction-associated steatotic liver disease (MASLD). We aimed to evaluate the effects of manufactured sugars (L-glucose) compared to natural sugars (D-glucose) on phenotype, molecular and metabolic changes in mice models fed with either regular diet (RD) or high fat diet (HFD). Methods: C57BL/6 mice fed 16-weeks with either RD; 70 % carbohydrate or HFD; 60% fat, with or without additional glucose (Glu, at 18% w/v) to drinking tap water at weeks 8-16; of either natural (D-Glu) or manufactured (L-Glu) sugars. Liver inflammation (ALT and AST serum levels, liver H&E histologic stains and cell viability profile by p-AKT), liver fibrosis (quantitated alpha smooth-muscle-actin (aSMA) by western blot and RT-PCR, Masson Trichrome staining (MTC) of liver tissue), liver lipid (steatosis stain by H&E, Adipose Differentiation-Related Protein (ADRP) lipid accumulation, serum and lipid peroxidation Malondialdehyde (MDA) markers by ELISA), glucose hemostasis (serum Glucose and C-peptide with HOMA-IR score calculation) and liver aspects (hepatic glucose transporter 2 (GLUT2), insulin receptor (IR) expressions and GYS2/PYGL ratio) evaluated. Results: D- and L- Glu supplementations propagate hepatocytes ballooning and steatosis in HFD-fed mice and were associated with aSMA down-expressions by 1.5-fold compared to the untreated group while showed an acceleration in liver fibrosis in the RD-fed mice. Lipid profile (Steatosis, ADRP and MDA) significantly increased in HFD-fed mice, both Glu supplementations (mainly the L-Glu) increased serum MDA while decreased ADRP. HOMA-IR score and IR significantly increased in HFD-fed mice, with further elevation in HOMA-IR score following Glu supplementations (mainly L-Glu). The increase in HOMA-IR negatively correlated with IR and Glut2 expressions. D- and L- Glu supplementations showed significant decrease of Glycogenesis (low GYS2/PYGL ratio) and unchanged p-AKT pattern compared to their RD counterparts. Conclusion: Our data indicate an increase in rate of de-novo lipogenesis (DNL) in RD-fed mice (High carbohydrate diet) and liver fibrosis following additional sugar supplementations. In contrast, HFD-fed mice (with pre-existing high lipid profile) supplemented with sugar showed less liver fibrosis, because of reduced de-novo fatty acids synthesis and subsequently, the lipid oxidation pathways become dominated and induce the net results of lipid clearance.